The role of classroom management and mastery goal orientation towards student’s self-regulation in learning Mathematics - Cahyani, Berliana Henu; Alsa, Asmadi; Ramdhani, Neila; Khalili, Fakher Nabeel (Psikohumaniora: Jurnal Penelitian Psikologi, 2019)
Mathematics until today is still considered a difficult subject so that it needs to think about appropriate strategies to encourage students to be able to regulate themselves in learning this subject. This study aimed to test empirically the role of classroom management and mastery goal orientation towards self-regulated learning. The participants of the study were 177 students of state high schools in Sleman, who were selected using a purposive sampling technique. The scales used were self-regulation of mathematics learning scale, classroom management scale, and mastery goal orientation scale. The data analysis using two-predictor regression analysis showed that classroom management and mastery goal simultaneously played a significant role by 68.7% (R2=0.687, F (2.177) =191.243, p<0.01). Classroom management predicted self-regulation (β= -0.130, p < 0.01), and so did mastery goal (β= 0.878, p < 0.01). Based on the results of this study, it could be concluded that self-regulation in learning Mathematics can be determined through classroom management and mastery goals concurrently.